Forage cactus-sorghum intercropping at different irrigation water depths in the Brazilian Semiarid Region - Diniz, Wellington Jairo da Silva; Silva, Thieres George Freire da; Ferreira, Jadna Mylena da Silva; Santos, Djalma Cordeiro dos; Moura, Magna Soelma Beserra de; Araújo, Gherman Garcia Leal de; Zolnier, Sérgio (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the productive performance, biological efficiency, and the competitive ability of the forage cactus-sorghum intercropping under different irrigation depths with saline water in the Brazilian Semiarid Region. The experiment was carried out in Serra Talhada, in the state of Pernambuco, between 2014 and 2015, in a randomized complete block design, with four replicates, and a 5x3 factorial arrangement in split plots, with one year of forage cactus cycle and two years of sorghum cycles. The plots were composed by four irrigation water depths based on the fractions of 25, 50, 75, and 100% of the reference evapotranspiration, besides dry conditions; and the subplots consisted of three cropping systems (single crop of forage cactus, single crop of sorghum, and intercropping of forage cactus-sorghum). The increase of water irrigation depths increased the yields of sorghum in single crop and of the forage cactus-sorghum intercropping. The intercropping system promoted production stability with a higher system productivity index (SPI) for forage cactus-sorghum intercropping (6,279.02 kg ha-1 DM) than for forage cactus in single crop (4,626.98 kg ha-1 DM). The relative density coefficient (12.33) was indicative of the great compatibility of the intercropping system. The forage cactus-sorghum association shows biological advantage and competitiveness capacity, with a higher productive index than their monocultures.